Turning waste into opportunity: Advancing circular and equitable waste management - Dolly Priatna; Kathryn A. Monk; Shujaul Mulk Khan; Hwan-Ok Ma; Irfan Aziz; Didik Notosudjono; Yoshikazu Tatemoto; Imran Ali (Universitas Pakuan, 2025)
The issue of waste management has emerged as a critical environmental and social challenge globally. Every day, billions of tons of waste are generated through human activities, much of which is inadequately managed. A 2018 report from the World Bank highlighted that over 2 billion tons of solid waste are produced annually, a figure projected to rise to 3.4 billion tons by 2050 without substantial changes in management practices. Waste accumulation is more than a matter of disposal; it triggers complex issues, including soil, water, and air pollution, as well as climate change, driven by greenhouse gas emissions like methane from landfills. In Indonesia, a populous nation with high consumption rates, waste management poses significant challenges. According to the Ministry of Environment and Forestry (KLHK), national waste generation in 2023 reached approximately 19 million tons annually, with only 60–70% collected and less than 10% recycled. Consequently, the majority of waste ends up in landfills—many of which still operate under open dumping systems that not only pollute the environment but also threaten the health of nearby communities. The escalating problem of plastic waste is particularly alarming. A research indicates that Indonesia is the second-largest contributor to marine plastic waste globally, following China. The plastic waste entering the ocean endangers marine ecosystems and can infiltrate the human food chain as microplastics. This situation underscores the need to view waste management not only as a technical challenge but as an interconnected social, economic, and governance issue.